Dinamika Kafa’ah Harta: Meninjau Ulang Kesetaraan Ekonomi dalam Fikih Klasik dan Kontemporer - Shoby Hatul Adha; Asfar Hamidi Siregar (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study examines the concept of kafa'ah (equality) in marriage, focusing on the aspect of property from the perspective of classical and contemporary Islamic jurisprudence. Kafa'ah is one of the important principles in determining the compatibility of a husband and wife, covering aspects of religion, lineage, social status, and economy. Along with the social and economic development of modern society, new dynamics have emerged in understanding the relevance of economic equality in building a harmonious family. This study uses a library research method, by reviewing Islamic jurisprudence literature from four schools of thought as well as the views of contemporary scholars such as Yusuf Qaradhawi and Sayyid Sabiq. The results of the study show that although there are differences of opinion among scholars regarding the importance of kafa'ah in the aspect of property, it is generally agreed that the aspects of religion and morality are the main considerations in marriage. However, in the context of modern life, economic equality can be considered as a supporting factor in realizing a stable family. Thus, kafa'ah in property should not be made an absolute requirement, but rather positioned as one of the rational considerations in choosing a life partner.